Taṭbīqāt Ta’līm al-Lughah al-Arabiyah li al-Nāṭiqīn bi al-ʿArabiyah wa bi Ghairihā al-Raqmiyah fī Madārīs al-Imārāt al-Waṭaniyah: Kaifiyatu Idārah ʿUrūḍihā wa Taghziatihā al-Rājiʿah - Ahdab Abd El Wahab (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Applications of teaching Arabic to native and non-Arabic speakers in Emirates National Schools: how to manage their offerings and what is their feedback. Emirates National Schools strive to keep pace with technical progress and consider the rapid knowledge development in the light of the knowledge economy, in various educational and learning fields, especially in the field of teaching Arabic to native speakers and others. In this research, we will try to monitor experiences and experiences in this regard, to benefit from them in improving the digital performance of teaching Arabic to non-native speakers, aiming to: introduce the smart applications used in schools and manage their educational offerings, and indicate the characteristics of the supporting applications in order to identify the learner’s tasks and performance and how to provide feedback.تسعى مدارس الإمارات الوطنية لمواكبة التقدم التقني ومراعاة التطور المعرفي المتسارع في ظل اقتصاد المعرفة، في مختلف الحقول التعليمية والتعلُّمية، خاصة في مجال تعليم اللغة العربية للناطقين بها وبغيرها فقد أنشأت عدداً من منصات التعليم وتطبيقات الأجهزة الذكية لذلك، واكتسب معلموها خبرة في الإعداد والتنفيذ والتقويم والتطوير، وسنحاول في هذا البحث رصد الخبرات والتجارب في هذا الصدد ،للإفادة منها في تجويد الأداء الرقمي لتعليم اللغة العربية للناطقين بغيرها، هادفين إلى: التعريف بالتطبيقات الذكية المستخدمة في المدارس وإدارة عروضها التعليمية، وبيان سمات التطبيقات الداعمة بغرض الوقوف على مهمات المتعلم وأدائه وكيفية التغذية الراجعة وما لازم ذلك من إيجابيات وسلبيات.